Airborne contamination in an operating suite: report of a five-year survey. - Suzuki, A. (Cambridge University Press, 1984)
Airborne contamination in an operating suite was studied with a slit sampler, settle plates and a light-scattering particle counter. In conventional operating rooms there was a significant difference between the empty rooms and rooms in use; the mean total bacterial count by a slit sampler changed from 1.1 in empty to 42.5 c.f.u./m3 in use (39 times increase), the settle plates count changed from 1.5 to 17.4 c.f.u./m2/min (12 times increase), and the mean total particle count changed from 56.9 to 546.7/l (10 times increase) respectively. The increase was caused mainly by persons present in the room. Another difference was found between zones in the operating suite; the bacterial count in the clean area doubled in the semi-clean area and further doubled in the dirty area in slit sampler count as well as settle plates count, and particle count in the clean area increased by 14 times in the semi-clean and dirty areas. This difference resulted from the different quality of the ventilating system. Air cleanliness of operating rooms in use by persons present in the room dropped to a level between the clean and the semi-clean area in spite of the high quality of the ventilating system. Bacterial species identified were mostly coagulase negative staphylococci and micrococci. Our study indicates that reduction of airborne contamination in an operating suite is accomplished by the combination of an efficient ventilating system and the restriction of the number of persons present in the room.